2001
DOI: 10.1207/s15327078in0204_09
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Via Maternal Touch

Abstract: The study of emotion elicitation in the caregiver-infant dyad has focused almost exclusively on the facial and vocal channels, whereas little attention has been given to the contribution of the tactile channel. This study was undertaken to investigate the effects of touch on infants' emotions. During the time that objects were presented to the dyad, mothers provided tactile stimulation to their 12-month-old infants by either (a) tensing their fingers around the infants' abdomen while abruptly inhaling, (b) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…Similar results have been reported in several other social referencing studies as well (e.g., L. J. Carver & Vaccaro, 2007;Hertenstein & Campos, 2001;Hornik et al, 1987). Furthermore, Klinnert et al's (1986) study (discussed in section 1a), which did not reveal a negativity bias in 12-month-olds' social referencing behavior, did suggest such a bias in infants' affect.…”
Section: B the Negativity Bias In Emotional Contagionsupporting
confidence: 85%
“…Similar results have been reported in several other social referencing studies as well (e.g., L. J. Carver & Vaccaro, 2007;Hertenstein & Campos, 2001;Hornik et al, 1987). Furthermore, Klinnert et al's (1986) study (discussed in section 1a), which did not reveal a negativity bias in 12-month-olds' social referencing behavior, did suggest such a bias in infants' affect.…”
Section: B the Negativity Bias In Emotional Contagionsupporting
confidence: 85%
“…Although the systematic study of maternal and infant touch has been widely neglected (Malphurs, Raag, Field, Pickens,& Pelaez-Nogueras, 1996;Pelaez-Nogueras et al, 1996;Hertenstein & Campos, 2001;Hertenstein, 2002), recent research on tactile stimulation demonstrates that maternal touch is an important means of communication during early social exchanges. Touch elicits positive affect, reduces negative affect, and modifies overall responsiveness in infants as early as 3 months of age (Stack & Muir, 1990Pelaez-Nogueras et al, 1996;Stack & Arnold, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When a female experimenter was interacting with a child and while making eye-contact also applied a touch, it was found that stroking touches resulted in the child making eye-contact more often, vocalizing more, smiling more, and crying and protesting less [398] [see also 400]. Conversely, in another study, when a mother touched her infant more roughly, in this particular case by clenching her hands around the child's abdomen, the child responded with more negative emotional expressions and less confident behavior [243]. Another type of touch that may be particularly beneficial in mother-child interactions is massaging touch.…”
Section: Physical and Emotional Well-beingmentioning
confidence: 98%